Extending the Indications of 5-Aminolevulinic Acid for Fluorescence-Guided Surgery for Different Central Nervous System Tumors: A Series of 255 Cases in Latin America - Silva Jr, Erasmo Barros da; Ramina, Ricardo; Coelho Neto, Maurício; Machado, Guilherme Augusto de Souza; Cavalcanti, Marcella Santos; Silva, Joseph Franklin Chenisz da (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Introduction Fluorescence guidance with 5-aminolevulinic acid (5-ALA) is a safe and reliable tool in total gross resection of intracranial tumors, especially malignant gliomas and cases of metastasis. In the present retrospective study, we have analyzed 5-ALA-induced fluorescence findings in different central nervous system (CNS) lesions to expand the indications of its use in differential diagnoses.Objectives To describe the indications and results of 5-ALA fluorescence in a series of 255 cases.Methods In 255 consecutive cases, we recorded age, gender, intraoperative 5-ALA fluorescence tumor response, and 5-ALA postresection status, as well the complications related to the method. Postresection was classified as ‘5-ALA free’ or ‘5-ALA residual’. The diagnosis of histopathological tumor was established according to the current classification of the World Health Organization (WHO).Results There were 195 (76.4%) 5-ALA positive cases, 124 (63.5%) of whom underwent the ‘5-ALA free’ resection. The findings in the positive cases were: 135 gliomas of all grades; 19 meningiomas; 4 hemangioblastomas; 1 solitary fibrous tumor; 27 metastases; 2 diffuse large B cell lymphomas; 2 cases of radionecrosis; 1 inflammatory disease; 2 cases of gliosis; 1 cysticercosis; and 1 immunoglobulin G4-related disease.Conclusion Fluorescence with 5-ALA can be observed in lesions other than malignant gliomas or metastases, including meningiomas, hemangioblastomas, pilocytic astrocytomas, and lymphomas. Although there is need for further evidence for the use of 5-ALA beyond high-grade gliomas, it may be a safe and reliable tool to improve resection in positive tumors or to guide the histopathologic analysis in biopsies.
Keywords: 5-aminolevulinic acid; brain cancer; extent of resection